IC Design Of A Passive RFID Transponder With The Implementation Of Internal Mixed Signal ESD Protection Circuit - Khaw, Mei Kum (2008)
This thesis is divided into two parts. In the first part, comprehensive literature studies are performed on the evaluation of RFID designs of transponders, readers, antennas and systems. Lastly, a performance comparison of RFID operating at two popular frequencies; High Frequency (HF) and Ultra High Frequency (UHF) is given and their pros and cons are analyzed.